In the shadow of HIV & TB: A commentary on the COVID epidemic in South Africa. Issue 8 (2nd August 2020) - Bulled, Nicola; Singer, Merrill
ABSTRACT: While COVID-19 has become a global pandemic that has spread to all regions of the globe, local historic, health, and socio-environmental factors shape the epidemiological contours, response, and social challenges present within each affected nation. Thus, while countries like China, Italy, Iran, Brazil, and the United States have all been hard hit by the pandemic, there are critical differences across these nations in a number of variables (e.g. demographic features, health histories, healthcare systems, infection case rates, case fatality rates, national responses). In other words, within the global pandemic there are multiple importantly distinct national epidemics. Overcoming the grave threats to public health presented by COVID-19 requires both international cooperation and country-specific efforts that reflect local histories, needs, and resources. Already concerns are being expressed among health officials about how COVID-19 might be devastating in Africa. Currently, South Africa has the highest number of diagnosed COVID-19 cases on the continent and has been identified as being at high risk in the pandemic. This paper examines the public health response to the COVID-19 threat, how the prior and ongoing HIV and TB epidemics shape the COVID-19 epidemic and influence the response, and the potential ramifications of the response.